Border politics the limits of sovereign power - Vaughan-Williams, Nick (Edinburgh University Press, 2009)
This book presents a distinctive theoretical approach to the problem of borders in the study of global politics. It turns from current debates about the presence or absence of borders between states to consider the possibility that the concept of the border of the state is being reconfigured in contemporary political life.